Climate Change and Floating Farming: Sustainable Livelihood Strategy in Bangladesh - Sukanta Sarkar (International Journal of Climate Conditions, 2025)
The paper discussed the significance of floating farming in Bangladesh. It has found that the tradition of growing vegetables, fruits and spices on rafts has now become a solution for farmers to cope with extreme weather conditions, floods and rising seas. Land cultivation is becoming more popular among farmers in many regions due to high market prices. Floating bed cultivation has now been extended to wet and intermittently irrigated areas in southern Bangladesh. Vegetables and other horticultural crops are now grown in this method and its popularity is increasing. The current farming system offers the local people a variety of health, wellness and agricultural activities that are beneficial to local people. Women play a significant role in these changes but are often overlooked in Bangladeshi society. While floating gardens have been successful for many, there are still those who have not benefited from this farming technique. The cost of setting up a garden is low, requiring only a small investment in fertilizer, seeds, and the work required to make the garden. Floating gardens are just one way that people living and working in Bangladesh can improve their food supply, and small water can play a significant role. Floating bed culture is considered an alternative lifestyle. Therefore, there should be more cooperation from the agriculture department and other organizations for expansion of such cultivation in flood prone and water logging districts of the country.
Keywords: Climate change; Farmers; floating farming; income; natural calamities